2015
DOI: 10.1093/femsle/fnv049
|View full text |Cite
|
Sign up to set email alerts
|

Allicin from garlic inhibits the biofilm formation and urease activity of Proteus mirabilis in vitro

Abstract: Several virulence factors contribute to the pathogenesis of Proteus mirabilis. This study determined the inhibitory effects of allicin on urease, hemolysin and biofilm of P. mirabilis ATCC 12453 and its antimicrobial activity against 20 clinical isolates of P. mirabilis. Allicin did not inhibit hemolysin, whereas it did inhibit relative urease activity in both pre-lysed (half-maximum inhibitory concentration, IC50 = 4.15 μg) and intact cells (IC50 = 21 μg) in a concentration-dependent manner. Allicin at sub-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 52 publications
4
23
0
Order By: Relevance
“…This result suggests that hydrophobic compounds extracted from garlic might have activity as a QSI (47). Allicin prevents biofilm formation by inhibiting early bacterial adhesion and EPS secretion (42,48,49). In addition, allicin inhibits the secretion of virulence factors by regulating QS (50).…”
Section: Effects Of Sulfur Compounds On Biofilm Formation and Quorum mentioning
confidence: 94%
“…This result suggests that hydrophobic compounds extracted from garlic might have activity as a QSI (47). Allicin prevents biofilm formation by inhibiting early bacterial adhesion and EPS secretion (42,48,49). In addition, allicin inhibits the secretion of virulence factors by regulating QS (50).…”
Section: Effects Of Sulfur Compounds On Biofilm Formation and Quorum mentioning
confidence: 94%
“…Allicin, a thiosulfinate from garlic (Allium sp.) and curcumin, the active ingredient in turmeric, also inhibited the urease from P. mirabilis (Prywer and Torzewska 2012;Ranjbar-Omid et al 2015), but showed relatively little inhibitory activity towards the staphylococcal enzyme. The extracts of horseradish (Armoraciae rusticanae) and broccoli (B. oleracea) contain sulforaphane and other isothiocyanates that reduced the urease activity from H. pylori (Fahey et al 2013), but these preparations also had no effect of the enzyme from S. saprophyticus.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, allicin exhibited antimicrobial activity against P. mirabilis by inhibiting urease activity. Relative urease activity in both prelysed and intact cells was inhibited by allicin in a concentration-dependent manner [44].…”
Section: Antimicrobial Activitymentioning
confidence: 98%
“…Act through Akt/eNOS pathway [30] Mediate Nrf2 nuclear translocation [36] SAC Inhibit calpain via decreasing the level of intracellular Ca2+ [32] DADS Regulate ERK, BDNF and CREB signaling [35] Z-ajoene Reduce lipid peroxidation [37] Microbial diseases Allicin Inhibit Bcc by targeting its thiol [41] Show synergistic activity with AgNPs [43] Inhibit urease activity [44] Diabetes Allicin Reduce autoantibodies, anti-islet cell antibodies [45] SAC Decrease oxidative stress [46] Activate peroxisome proliferator activated receptor [47] High cholesterol Allicin Inhibit squalene-monooxygenase, acetyl-CoA synthetase, etc. [23] Suppress apoptosis and oxidative stress pathway [48] and anti-islet cell antibodies (ICA) in type 1 diabetes (IDDM).…”
Section: Allicinmentioning
confidence: 99%